Quark-hadron deconfinement phase transition and massive hybrid stars - Atta, Debasis; Singh, Vinay; Basu, D. N. (Indian journal of physics, 2024)
The stellar configurations of quark stars have been studied using perturbative QCD (pQCD). The effective equation of state (EoS) for cold quark matter from pQCD has been used which goes beyond the MIT bag model description. The neutron star structures with EoS obtained from NRAPR Skyrme interaction have also been explored. The quark-hadron deconfinement phase transition in matter under extreme pressure in stellar interior has been studied using Maxwell construction. The influence of hybrid EoS on the jump in energy density has been investigated. To study hybrid stars, the NRAPR hadronic model and pQCD EoS for the quark phase have been used. The effects of the different parameters of the pQCD model on the structural properties of Quark stars and Hybrid stars have been investigated in light of various recent astrophysical observations. The mass-radius variation of Quark stars, Neutron stars and Hybrid stars with quark matter cores in the context of twin stars and appearance of special points have been studied.